Cognitive Behavioral Therapy for Insomnia, Mindfulness, and Yoga in Patients With Breast Cancer with Sleep Disturbance: A Literature Review - Simon B Zeichner (Breast Cancer: Basic and Clinical Research, 2017)
The number of patients with breast cancer diagnosed with sleep disturbance has grown substantially within the United States over the past 20 years. Meanwhile, there have been significant improvements in the psychological treatment of sleep disturbance in patients with breast cancer. More specifically, cognitive behavioral therapy for insomnia (CBT-I), mindfulness, and yoga have shown to be 3 promising treatments with varying degrees of benefit, supporting data, and inherent limitations. In this article, we will outline the treatment approach for sleep disturbance in patients with breast cancer and conduct a comprehensive review of CBT-I, mindfulness, and yoga as they pertain to this patient population.